2021
DOI: 10.3390/electronics10141611
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation Systems for Education: Systematic Review

Abstract: Recommendation systems have emerged as a response to overload in terms of increased amounts of information online, which has become a problem for users regarding the time spent on their search and the amount of information retrieved by it. In the field of recommendation systems in education, the relevance of recommended educational resources will improve the student’s learning process, and hence the importance of being able to suitably and reliably ensure relevant, useful information. The purpose of this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 107 publications
(116 reference statements)
0
37
0
Order By: Relevance
“…According to many recent studies, the lack of specialists in certain areas causes economic damage to states. This situation is especially critical during the COVID-19 pandemic ( The Economist 2022 ; Tømte et al 2019 ; Tungpantong et al 2021 ; Unified State Electronic Database on Education 2022 ) and the ongoing war in Ukraine and its economic implications ( Urdaneta-Ponte et al 2021 ; Valkanas and Diamandis 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to many recent studies, the lack of specialists in certain areas causes economic damage to states. This situation is especially critical during the COVID-19 pandemic ( The Economist 2022 ; Tømte et al 2019 ; Tungpantong et al 2021 ; Unified State Electronic Database on Education 2022 ) and the ongoing war in Ukraine and its economic implications ( Urdaneta-Ponte et al 2021 ; Valkanas and Diamandis 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Information recommendation is a method for students to quickly and effectively screen out the objects that meet their preference characteristics from the mass objects. At present, information recommendation technology is widely used in many fields [ 3 ]. It is an effective way to solve the problem of “information trek” to apply information recommendation technology to online education and realize personalized recommendation of innovation and entrepreneurship education resources in universities in the process of online education.…”
Section: Introductionmentioning
confidence: 99%
“…In the systematic review presented by [19], attention should be drawn to the work shown in Table 1 in this area. In some cases, ML is used in RSs to make inferences about how past actions correspond to future outcomes.…”
Section: Introduction and Related Studiesmentioning
confidence: 99%